2021
DOI: 10.1088/1755-1315/820/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Summary and Trend Analysis of Research Progress on Granular Slope Geological Hazards

Abstract: There are a large number of granular slope mixture geological disasters in the alpine mountainous areas in western China. Their structural characteristics are significantly different from the general slopes. They have the characteristics of poor self-stability, high suddenness and strong recurrence. With the continuous development of the western region of the country, such geological disasters have received close attention from scholars at home and abroad. This article first summarized and analyzed the basic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…3b). Several studies have been carried out to model granular flows against rigid barriers by performing indoor experiments (Faug 2015) and analogue simulations (Albaba et al 2015;Gray 2018;Xie et al 2021). Pudasaini et al (2007) performed a laboratory test and concluded that the maximum impact force is an important factor to consider when designing a rigid barrier.…”
Section: Introductionmentioning
confidence: 99%
“…3b). Several studies have been carried out to model granular flows against rigid barriers by performing indoor experiments (Faug 2015) and analogue simulations (Albaba et al 2015;Gray 2018;Xie et al 2021). Pudasaini et al (2007) performed a laboratory test and concluded that the maximum impact force is an important factor to consider when designing a rigid barrier.…”
Section: Introductionmentioning
confidence: 99%